Personnel recognition based on multistatic micro‐Doppler and singular value decomposition features. Issue 25 (1st December 2015) - Fioranelli, F.; Ritchie, M.; Griffiths, H.
Abstract : The use of micro‐Doppler signatures experimentally collected by a multistatic radar system to recognise and classify different people walking is discussed. A suitable feature based on singular value decomposition of the spectrograms is proposed and tested with different types of classifiers. It is shown that high accuracy of between 97 and 99% can be achieved when multistatic data are used to perform the classification.